IsoDAR@Yemilab: A report on the technology, capabilities, and deployment. (1st September 2022) - Alonso, J.R.; Conrad, J.M.; Winklehner, D.; Spitz, J.; Bartoszek, L.; Adelmann, A.; Bang, K.M.; Barlow, R.; Bungau, A.; Calabretta, L.; Kim, Y.D.; Mishins, D.; et al.
Abstract: IsoDAR@Yemilab is a novel isotope-decay-at-rest experiment that has preliminary approval to run at the Yemi underground laboratory (Yemilab) in Jeongseon-gun, South Korea. Here, we describe in detail the considerations for installing this compact particle accelerator and neutrino target system at the Yemilab underground facility. Specifically, we describe the caverns being prepared for IsoDAR, and address installation, shielding, and utilities requirements. To give context and for completeness, we also briefly describe the physics opportunities of the IsoDAR neutrino source when paired with the Liquid Scintillator Counter (LSC) at Yemilab, and review the technical design of the neutrino source.